Multinominal bioindication for the evaluation of urban environment condition – case study of the city of Kherson - M. M. Radomska; A. V. Husieva; I. V. Horobtsov (Науковий вісник НЛТУ України, 2020)
The urban environment is one of the most complicated man made systems, which condition and status are hard to define, but it is essential for the survival of humans. Among the methods of the urban environment condition evaluation bioindication is one of the most simple and able to provide valuable dose-response information for efficient management of environmental safety. Being such a useful method, the bioindication has a range of disadvantages, due to dependence on single species response, which can lie within the acceptable amplitude of living fluctuations or is conditioned by factors other than human activity. Most of the researches of such type stick to one single species and attempt to build clear impact-response dependencies for specific conditions. The paper considers the possibility to combine bioindicators from different taxonomic groups in one study to receive more reliable vision of the environment status. The typical combination offered in the study is phytoindication and lichen indication, which relies on measuring plants morphological parameters and lichen diversity and distribution. The research was conducted in the city of Kherson, previously considered relatively unpolluted. The territory of the city was analyzed to define the most affecting sources of environment pollution. The background area was chosen to verify the changes in the parameters of bioindicators. The results showed that the level of anthropogenic pressure within the urban territory is considerable and demands mitigation actions, aimed at improvement of air pollution control, waste management, traffic organization and implementation of remediation activities at decommissioned facilities. The deviations between the results of lichen indication and phytoindication gave possibility to infer the possible sources and composition of pollution, thus providing basis for efficient environment protection solutions to be implemented. The paper also presents the recommendations on the combination of bioindicators to be used in various studies, depending on the purpose and type of the ecosystem under investigation. The sequence of the data processing must include the comparative analysis of the information obtained to use the differences between the results provided by different organisms for clarification of the human impacts parameters.